THE COLOR REVOLUTION PHENOMENON: ROM CLASSICAL THEORY TO UNPREDICTABLE PRACTICES - TASTENOV, Alisher (CENTRAL ASIA AND THE CAUCASUS, 2007)
Between 2003 and 2005, a relatively new trend—the transformation of political regimes in some of the Soviet successor states, coined in political science as “velvet revolution”—became obvious in the post-Soviet expanse. The normally evolutionary dynamics of regime changes were moving at an accelerated pace toward the use of force, which echoed across the post-Soviet territory. The term “revolution” was applied to several interconnected events, starting with the dissatisfaction of a large number of citizens with the elections and their results produced by the government’s interference in the form of abuse of the administrative resource and cheating; the losers’ ability to mobilize the discontented voters; and encouragement from Western leaders and the public, which made it impossible to use force against the rallies, and ending with the op-position coming to power after a series of mass street actions. In the past, the expert community believed there were various reasons why Central Asia was less prone to fall victim to this phenomenon than Georgia and Ukraine. The events of March 2005 in Kyrgyzstan and of May 2005 in Uzbekistan demonstrated that the velvet revolution phenomenon was spreading far and wide and that it may destabilize all the other Central Asian countries.Recent developments have taught us that socio-political destabilization may develop into a protracted and unpredictable process. Obviously, the phenomenon calls for, whereby the results should be compared with reality and common political, social, economic, and geopolitical re-percussions identified. An analysis of the “revolutionary regime change” in Georgia, Kyrgyzstan, and Ukraine makes it possible to pro-vide a certain theoretical explanation of the phenomenon.